The techniques of violin playing. Die spieltechnik der violine - Arditti, Irvine; Platz, Robert HP (Kassel Bärenreiter, 2013)
Irvine Arditti who is an extraordinary violinist, a specialist for contemporary music and the leader of the phenomenal Arditti Quartet, worked together with the composer and conductor Robert HP Platz to produce this book on contemporary violin technique. It presents detailed explanations of the technical possibilities of the violin for performers and composers.This publication takes into account the virtuosity of a new generation of soloists. These are soloists who with their exceptional ability, have succeeded in paving the way for a greater understanding of classical and contemporary music.The chapters on bowing techniques, vibrato, pizzicato, glissando, flageolet, tablatures, rhythm and electronic sound production are illustrated with numerous musical examples and diagrams.Particularly helpful is the accompanying DVD, where Arditti demonstrates and explains the described techniques. Chapters on the basics of violin technique and on Irvine Ardittis personal experience with notable composers make the book equally interesting for non-violinists.
Contains a CD
Keywords: Violin; Method